Kombinasi Akupunktur dan Bekam dengan Ayub Stomping, Motor Imagery dan ROM Aktif Pasif terhadap Perubahan Skala Stroke (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the effectiveness of a combination of acupuncture and cupping therapy with the Ayub Stomping intervention method, Motor Imagery, and active-passive Range of Motion (ROM) exercises on changes in the stroke scale in stroke patients at Holistic Nursing Therapy Probolinggo. The method used was an experiment with a population of 155 patients and a sample of 112 respondents selected through purposive sampling techniques. The instrument used a stroke scale questionnaire, with data analysis using the Wilcoxon and Kruskal-Wallis tests. The results showed that Motor Imagery therapy (TKM) provided clinical improvement but was not statistically significant (p = 0.317). In contrast, active-passive ROM therapy (TKR) was effective in reducing stroke severity significantly (p = 0.025). Complementary nursing therapy (TKK) was also proven significant (p = 0.007), with an increase in the number of patients in the mild category. Ayub Stomping therapy (TKA) showed the most important results (p = 0.000), with 50% of patients experiencing an increase to the mild category. Kruskal-Wallis test showed significant differences between intervention groups (p = 0.000). Conclusion: Ayub stomping therapy is the most effective method in reducing stroke severity and improving stroke patient rehabilitation outcomes. Keywords: Acupuncture, Ayub Stomping, Cupping, Motor Imagery Rehabilitation, Active-Passive ROM, Stroke